Current political dynamics in Asia: Issues, developments and threats - Mahmood Sohail (Međunarodni Problemi)
The author examines the current political dynamics in Asia and the potential threat situations jeopardizing the regional security. The article looks at proliferation of nuclear weapons and the North Korean and the Iranian nuclear cases. It studies the international pressures, diplomacy moves and the Iranian reaction and the EU and American perceptions. The Taiwan issue and territorial dispute of the South China Sea and the problem of Kashmir between Pakistan and India are discussed. The regional radical terrorism networks under the Islamic guise are also examined.